Florisgrafía: Modos de hacer en la producción gráfica. Investigación de soportes alternativos y orgánicos en la práctica artística contemporánea - Pozo, Luciano (2022)
Reflection and research on the artistic praxis of a personal process that comes from a poetic practice and research. lt is an epistemological aspect materialized through words and writing. lt deals with the deepening of the research on the personal graphic creation. l present what l call florisgrafia as a personal graphic procedure. This way of making became a graphic procedure and later on a practice that made possible the creation of graphic pieces according to poetic and methodological approaches.